Absent in melanoma 2 suppresses gastric cancer cell proliferation and migration via inactivation of AKT signaling pathway - Dong Wang (Nature Portfolio, 2021)
Abstract Gastric cancer (GC) is the third leading cause of cancer-related mortality worldwide, and poses a great threat to public health. Absent in melanoma 2 (AIM2), a member of the pyrin-HIN family proteins, plays various roles across different types of cancers. However, the possible role of AIM2 in GC, as well as the underling mechanisms, are equivocal and need to be further explored. Herein, we identified that AIM2 expression was significantly down-regulated in GC tissues. Furthermore, loss of AIM2 was significantly associated with tumor size, lymph node metastasis (LNM) and tumor, node, metastases (TNM) staging, as well as poor prognosis in GC patients. Knockdown of AIM2 in GC cells significantly promoted cellular proliferation and migration, whereas AIM2 overexpression did the opposite. Mechanistically, we discovered that AIM2 regulates the AKT signaling pathway. In fact, the enhanced proliferation and migration ability induced by AIM2 knockdown was partially impaired in cells treated with the AKT inhibitor. Overall, our findings suggests that AIM2 is an independent prognostic marker and highlights a new entry point for targeting the AIM2/AKT signaling axis for GC treatment.